The rise of chance in evolutionary theory : a pompous parade of arithmetic - Pence, Charles H. (Elsevier Academic Press, 2022)
The Rise of Chance in Evolutionary Theory: A Pompous Parade of Arithmetic explores a pivotal conceptual moment in the history of evolutionary theory: the development of its extensive reliance on a wide array of concepts of chance. It tells the history of a methodological and conceptual development that reshaped our approach to natural selection over a century, ranging from Darwin's earliest notebooks in the 1830s to the early years of the Modern Synthesis in the 1930s. Far from being a "pompous parade of arithmetic, as one early critic argued, evolution transformed during this period to make these conceptual and technical tools indispensable. This book charts the role of chance in evolutionary theory from its beginnings to the earliest days of modern evolutionary theory, making it an ideal resource for evolutionary biologists, historians, philosophers, and researchers in science studies or biological statistics.